1949
DOI: 10.1021/ie50471a013
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Diammonium Phosphate Fertilizer

Abstract: Tennessee Valley Authority, Wilson Dam, Ala. r)iammonium phosphate, produced from anhydrous ammonia and electric-furnace phosphoric acid in a pilot plant using a new, saturator-type process, consisted of aggregates of thin tabular crystals bonded by a film of fine crystals. The product contained 0 to 5% of monoammonium phosphate, but otherwise was substantially free of impurities. Laboratory tests showed the product to be strong enough to withstand ordinary fertilizer handling without excessive degradation, sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1950
1950
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…The recommended conditions for the manufacture of diammonium phosphate using the vacuum crystallization process were ammoniation of H3P04 to pH 6.5, w'ith a maximum dryer temperature of 80°C. The properties of the diammonium phosphate fertilizers have been investigated by Thompson et al (8). Young, Hicks, and Davis (77) reported ammonia loss from 18-20-0 (18-46-0), during drying, of 2 to 3% at 82°C.…”
Section: Bridget• Andmentioning
confidence: 99%
“…The recommended conditions for the manufacture of diammonium phosphate using the vacuum crystallization process were ammoniation of H3P04 to pH 6.5, w'ith a maximum dryer temperature of 80°C. The properties of the diammonium phosphate fertilizers have been investigated by Thompson et al (8). Young, Hicks, and Davis (77) reported ammonia loss from 18-20-0 (18-46-0), during drying, of 2 to 3% at 82°C.…”
Section: Bridget• Andmentioning
confidence: 99%
“…This was done to understand the comparative efficacy of using nano-formulations over bulk materials and to test if nano-formulations are needed in lower amounts for fertilizer applications. Of these bulk controls, PA forms a soluble phosphorus control studied previously on Lactuca sativa (lettuce) [ 16 ] against P-based NMs, DAP has been conventionally used bulk P fertilizer [ 37 , 38 , 39 ] and RP provides a bulk control for nP and has also been used as a common source for deriving P fertilizers [ 10 ]. Their suspensions were used for irrigation of the plants.…”
Section: Methodsmentioning
confidence: 99%
“…The authors acknowledge the substantial contributions to the over-all sodium, and phosphate. Several other investigators have studied the flame photometric determination of potassium and observed that various anions affect the intensity of the potassium line (7,2,6,8).…”
Section: Acknowledgmentmentioning
confidence: 99%
“…Monoammonium phosphate fertilizer has been made commercially in Canada since 1931 and in the United States since 1946 from ammonia and wet-process phosphoric acid by a process described by Atwell (7). That process is unattractive for production of diammonium phosphate because of the high vapor pressure of ammonia over diammonium phosphate solutions, which can result in excessive loss of ammonia at the temperatures encountered.…”
mentioning
confidence: 99%
See 1 more Smart Citation